SURAU LANSEK FENOMENA SAKRAL DAN PROFAN (STUDI PERILAKU MASYARAKAT TERHADAP SURAU LANSEK DI KORONG KOTO PANJANG NAGARI III KOTO AUR MALINTANG SELATAN KECAMATAN IV KOTO AUR MALINTANG KABUPATEN PADANG PARIAMAN) - Rini Mardiyarni; T. Romi Marnelly (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
This research was conducted in Korong Koto Panjang Nagari III Koto South Aur MalintanG in IV Koto Aur Malintang District Padang Pariaman Regency. The purpose of this research is to know wahat are the Sacred and Profane objects as well as the society and the implementation of the praying ritual in Surau Lansek. The technique of determining samples by purposive samples and determine the number of samples of 7 (seven) people. The method used in this research is Descriptive Qualitative research method and data instrument is observation, interview, and documentation. Based on the results of research, the writer knows Surau Lansek as magical Surau and there are sacred object as pole “macu”, shells, and biliak tuangku hitam and profane a kolah and paluang. The arrival of the people to this surau to release his intention or pay his vows in the form of money, rice. Rice, and a goat and holding ritual pray together with burning incense then continued with eating together and the community in question is a visitor who come more than five times. Religious behavior of people believe in the surau from ancestors first and afraid of arrogance because this has become a habit of the community for generations in IV Koto Aur Malintang district.Keywords : Surau Lansek, Sacred, Profane, and Behavior